1979
DOI: 10.1042/bj1770237
|View full text |Cite
|
Sign up to set email alerts
|

The role of link-protein in the structure of cartilage proteoglycan aggregates

Abstract: Proteoglycan fractions were prepared from pig laryngeal cartilage. The effect of link-protein on the properties of proteoglycan-hyaluronate aggregates was examined by viscometry and analytical ultracentrifugation. Aggregates containing link-protein were more stable than link-free aggregates at neutral pH, at temperatures up to 50 degrees C and in urea (up to 4.0M). Oligosaccharides of hyaluronate were able to displace proteoglycans from link-free aggregates, but not from the link-stabilized aggregates. Both ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
169
1
6

Year Published

1982
1982
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(182 citation statements)
references
References 23 publications
6
169
1
6
Order By: Relevance
“…The binding is through a specialized portion of their core protein, the hyaluronate-binding region [6], to a decasaccharide segment of the hyaluronate chain [9]. This interaction is stabilized by the binding of a small glycoprotein, the link protein [6,8], with affinity for both hyaluronate [9,10] and the hyaluronate-binding region of the aggrecan monomer, leading to the formation of a very stable ternary complex [11]. This model has been extended by a combination of electron microscopy [12][13][14] and sequence analysis at the protein [15] and cDNA [16][17][18][19][20] level.…”
Section: Introductionmentioning
confidence: 99%
“…The binding is through a specialized portion of their core protein, the hyaluronate-binding region [6], to a decasaccharide segment of the hyaluronate chain [9]. This interaction is stabilized by the binding of a small glycoprotein, the link protein [6,8], with affinity for both hyaluronate [9,10] and the hyaluronate-binding region of the aggrecan monomer, leading to the formation of a very stable ternary complex [11]. This model has been extended by a combination of electron microscopy [12][13][14] and sequence analysis at the protein [15] and cDNA [16][17][18][19][20] level.…”
Section: Introductionmentioning
confidence: 99%
“…When excess proteoglycan is added to the coat, the pore size of the pericellular matrix is decreased, with particles 0.3 microns or larger excluded [18]. Link proteins stabilize the interaction between hyaluronic acid and proteoglycans [19][20][21] and have been shown to have a shortening effect on the length of hyaluronan that is similar to the proteoglycan [17]. Others have shown that adding an excess of link proteins can cause fragmentation or disruption of hyaluronan networks [22].…”
Section: Pericellular Matrix Structurementioning
confidence: 99%
“…This protein was given the simple name 'link protein'. 7 The tripartite linkage of aggrecan, link protein and hyaluronan is essentially non-dissociating and non-displaceable under physiological conditions. This interaction represents the primary reason why chaotropic agents are necessary to extract aggrecan from cartilage.…”
Section: Introductionmentioning
confidence: 99%